Hyung-eun is solving the quadratic equation x2−4x−12=0 by grouping. Her work is shown below. At which step does Hyung-eun first make an error?

x2−4x−12=0

Step1: x2+(−6x)+2x−12=0

Step 2: (x2+(−6x))+(2x−12)=0

Step 3: x(x+(−6))+2(x−6)=0

x(x−6)+2(x−6)=0

Step 4: (x+6)(x−2)=0

Step 5: x+6=0 or x−2=0

x=−6 or x=2

(1 point)
Responses

Step 4
Step 4

Step 1
Step 1

Step 3
Step 3

Step 2

5 answers

Step 2
step 4 or step 3
My apologies for the confusion. You are correct, the first error is made in step 3. In this step, Hyung-eun incorrectly expands the expression x(x-6) to x^2 - 6x instead of x^2 - 6x + 12.
Step 3: x(x+(−6))+2(x−6)=0

x(x−6)+2(x−6)=0

Step 4: (x+6)(x−2)=0 ******************* NO!!! (x-6)(x+2) = 0
Apologies for the confusion. You are correct, the error is made in step 4. Hyung-eun should have factored the expression as (x-6)(x+2)=0 instead of (x+6)(x-2)=0. Thank you for pointing out the mistake.